How can mathematics be used to improve burn care? - Ginger Egberts; Fred Vermolen; Qiyao Peng; H.Ibrahim Korkmaz; Paul van Zuijlen (Burns Open)
Severe second-degree ‘partial thickness’ and third-degree ‘full thickness’ burns are characterized by damage to the dermal layer of the skin. In the dermis, specialized cells called fibroblasts play a crucial role in wound healing. These cells produce collagen, a protein that provides strength and structure to the skin. After burn injury, fibroblasts migrate to the injured area and start producing and depositing collagen to help repair the damaged tissue. While contraction is essential for closing the wound, it can also result in scar contraction (contractures), especially in more severe burns. This contraction creates stresses on the skin, which can deteriorate the mobility of joints near the burn.This article overviews the most recent research results in computer simulations of scar contraction after burns.